2012
DOI: 10.1002/jcb.24065
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of redox state and pancreatic beta‐cell function: Role of leptin and adiponectin

Abstract: Whereas oxidative stress is linked to cellular damage, reactive oxygen species (ROS) are also believed to be involved in the propagation of signaling pathways. Studies on the role of ROS in pancreatic beta-cell physiology, in contrast to pathophysiology, have not yet been reported. In this study we investigate the importance of maintaining cellular redox state on pancreatic beta-cell function and viability, and the effects of leptin and adiponectin on this balance. Experiments were conducted on RINm and MIN6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 51 publications
2
31
1
Order By: Relevance
“…While it is difficult to compare an in vivo effect caused by a tissue directly exposed to effective and known doses, this result is consistent with that obtained in our in vitro studies as the presence of a high concentration of leptin inhibited ovarian SOD activity. These results also support those obtained in other in vitro studies, where leptin caused an increase in ROS levels (Yamagishi et al 2001, Xu et al 2004, Chetboun et al 2012. Steroidogenesis is an important source of free radical production as the enzymes involved in the different steps in the biosynthesis of steroids (cytochrome P450 family and others) transfer electrons to different molecules producing ROS (Rapoport et al 1995, Hanukoglu 2006.…”
Section: Discussionsupporting
confidence: 80%
“…While it is difficult to compare an in vivo effect caused by a tissue directly exposed to effective and known doses, this result is consistent with that obtained in our in vitro studies as the presence of a high concentration of leptin inhibited ovarian SOD activity. These results also support those obtained in other in vitro studies, where leptin caused an increase in ROS levels (Yamagishi et al 2001, Xu et al 2004, Chetboun et al 2012. Steroidogenesis is an important source of free radical production as the enzymes involved in the different steps in the biosynthesis of steroids (cytochrome P450 family and others) transfer electrons to different molecules producing ROS (Rapoport et al 1995, Hanukoglu 2006.…”
Section: Discussionsupporting
confidence: 80%
“…In INS-1 clonal b-cells, adiponectin protected against palmitate-or ceramide-induced apoptosis even in cells in which AMPK function was impaired by overexpression of a dominant negative mutant of the enzyme (Holland et al 2011). Chetboun et al (2012), as mentioned earlier, also showed that adiponectin (and leptin) increased proliferation of clonal b-cells (RIN and MIN6) without affecting apoptosis. These effects appeared to involve generation of ROS possibly by inhibiting expression of antioxidant enzymes such as superoxide dismutase.…”
Section: Adiponectinsupporting
confidence: 56%
“…We also demonstrated that leptin decreased uncoupling protein 2 (UCP2) expression in these islets and this may contribute to an effect of the adipokine in ameliorating b-cell apoptosisfurther research in a clonal b-cell line from our group also showed an effect of leptin to alter the B-cell lymphoma 2/Bcl2-associated X protein (BCL2/BAX) expression ratio, which may also explain the reduction in apoptosis induced by this factor . By contrast, a recent study by Chetboun et al (2012) found no effect of leptin (or adiponectin) on apoptosis, although both adipokines caused a reactive oxygen species (ROS)-mediated increase in cell proliferation and leptin (but not adiponectin)-inhibited GSIS. This potential role of low levels of ROS in promoting b-cell mass may underline the importance of our aforementioned finding that leptin decreases UCP2 as this protein may also have a role in reducing ROS levels -generally thought to be beneficial to b-cells but possibly, in view of Chetboun et al's hypothesis, decreasing proliferation.…”
Section: Leptin: the 'First' Adipokinementioning
confidence: 79%
“…Along with the generation of ROS, relatively longterm exposure of MIN6 cells to insulin did appear to increase significantly the expressions of the antioxidant enzymes Cat and Gpx, as occurs with some other inducers of cellular stress (Tiedge et al 1997, Laybutt et al 2002, Palsamy & Subramanian 2010, Chetboun et al 2012, Bhakkiyalakshmi et al 2014, Tersey et al 2014, Vasu et al 2014. In contrast, the expressions of Sod1 and Sod2 were only slightly and not significantly increased by 24 and 48 h insulin exposure.…”
Section: :3mentioning
confidence: 79%
“…Alternatively, it is possible that insulin might directly alter the expression of these enzymes. Accordingly, we examined MIN6 cells for the effects of 100 nM insulin given for 24 and 48 h on expression of Sod1, Sod2, Cat and Gpx, which are the main antioxidant enzymes in pancreatic β cells (Laybutt et al 2002, Chetboun et al 2012, Bhakkiyalakshmi et al 2014. As shown in Fig.…”
Section: Insulin Does Not Appear To Directly Affect Antioxidative Enzmentioning
confidence: 99%